The Synergistic Effects of the Glutathione Precursor, NAC and First-Line Antibiotics in the Granulomatous Response Against Mycobacterium tuberculosis - Teskey, Garrett; Cao, Ruoqiong; Islamoglu, Hicret; Medina, Albert; Prasad, Chaya; Prasad, Ramaa; Sathananthan, Airani; Fraix, Marcel; Subbian, Selvakumar; Zhong, Li; Venketaraman, Vishwanath (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis (M. tb), the causative bacterial agent responsible for tuberculosis (TB) continues to afflict millions of people worldwide. Although the human immune system plays a critical role in containing M. tb infection, elimination proves immensely more challenging. Consequently, there has been a worldwide effort to eradicate, and limit the spread of M. tb through the conventional use of first-line antibiotics. Unfortunately, with the emergence of drug resistant and multi-drug resistant strains of M. tb the archetypical antibiotics no longer provide the same ascendancy as they once did. Furthermore, when administered, these first-line antibiotics commonly present severe complications and side effects. The biological antioxidant glutathione (GSH) however, has been demonstrated to have a profound mycobactericidal effect with no reported adverse consequences. Therefore, we examined if N-Acetyl Cysteine (NAC), the molecular precursor to GSH, when supplemented in combination with suboptimal levels of standalone first-line antibiotics would be sufficient to completely clear M. tb infection within in vitro derived granulomas from healthy subjects and individuals with type 2 diabetes (T2DM). Our results revealed that by virtue of immune modulation, the addition of NAC to subprime levels of isoniazid (INH) and rifampicin (RIF) was indeed capable of inducing complete clearance of M. tb among healthy individuals.